2015
DOI: 10.1002/ijch.201400165
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport Mediated by Peptides Immobilized on Surfaces

Abstract: The tetragonal compound FeF3(H2O)3 is synthesized through a facile liquid‐phase method. FeF3(H2O)3/C is prepared by mechanical milling with carbon black and investigated for its application as a cathode material. This material exhibits two types of thermodynamic lithiation scheme, at 3.0 and 1.5 V, which correspond to a Li+‐intercalation process (1 Li+) and a conversion reaction (>1 Li+), respectively. A reversible capacity of about 300 mAh g−1 can be achieved at a current density of 10 mAg−1. In particular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 134 publications
1
22
0
Order By: Relevance
“…The dipole moment of molecular species plays different roles of fundamental and applied significance. For example, different ET (or electron‐transport) rates have been found for opposite orientations of the peptides in SAMs; similar effects were observed for ET in freely diffusing donor–peptide–acceptor systems . Thermodynamics, however, could also be responsible for making ET rates different: as a matter of fact, we already showed that an oriented peptide dipole moment affects significantly the redox potentials of electroactive groups and gold clusters .…”
Section: Resultssupporting
confidence: 60%
“…The dipole moment of molecular species plays different roles of fundamental and applied significance. For example, different ET (or electron‐transport) rates have been found for opposite orientations of the peptides in SAMs; similar effects were observed for ET in freely diffusing donor–peptide–acceptor systems . Thermodynamics, however, could also be responsible for making ET rates different: as a matter of fact, we already showed that an oriented peptide dipole moment affects significantly the redox potentials of electroactive groups and gold clusters .…”
Section: Resultssupporting
confidence: 60%
“…Here the free energy difference (DG) ij is approximated by the energy gap (DE) ij . The overall electron transfer rate constant for a two-step sequential hopping pathway was then calculated using a previously reported kinetic model, 10 that assumes steady-state occupation probability for different diabatic states (see eqn (4) and (5)). The outer-sphere reorganization energy (l) outer,ij from the diabatic state (i)to the neighboring diabatic state (j) is given by 45…”
Section: Computational Detailsmentioning
confidence: 99%
“…4 However, one must rst understand and subsequently be able to predict and control the associated charge transfer mechanisms. 5 Two main modes, superexchange (tunnelling) and thermally activated hopping, are widely accepted. 6 The superexchange mechanism of electron transfer involves direct molecule-mediated tunnelling, where the intervening peptide chain between electron donor and acceptor takes on a virtual role.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding electron transport through biomolecules is important, because they play central roles in cellular respiration, photosynthesis and enzymatic reactions. [1][2][3][4][5][6][7] Although much effort has been devoted to transport in peptides, 8,9 the exact mechanism of charge transport through peptides and proteins is still under debate. Generally, it is accepted that quantum tunnelling through molecular orbitals is the dominant mechanism for short peptide chains 10,11 and consequently their electrical conductance G decays exponentially with length as G = Ae −βl , 12,13 where the prefactor A is a constant reflecting the molecule-electrode coupling strength, l is the separation between two electrodes and β is an attenuation constant.…”
Section: Introductionmentioning
confidence: 99%